New Business Ventures And The Entrepreneur - Roberts Michael J (McGraw -Hill, 2006)
Roberts’ New Business Ventures and the Entrepreneur, 6e stands out as a text designed to guide tomorrow’s entrepreneurs down the difficult road ahead. Specifically, the Roberts team addresses the entrepreneur before, during and after the decision to create a new venture. Entrepreneurs need to realize that they are assuming a managerial role- both in a product and people sense. New Business Ventures, 6e will leave students with the skills needed to grasp and implement the general managerial responsibilities required to be a successful entrepreneur. The text provides an innovative approach to teaching the core general management skills via the lens of the entrepreneur. The course upon which this book I based is now the new core required course in general management at Harvard Business School.